The Influence of Soft Skills, Interests, and Motivation on Work Readiness Among Generation Z in Yogyakarta - Sulistya Rian Utami; Heri Prasetyo (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to determine how soft skills, interests, and motivation influence Generation Z's readiness to enter the workforce in Yogyakarta. The method used in this study is a quantitative approach with multiple linear regression analysis. A sample of 100 respondents was obtained through random sampling. The data collection tool was a questionnaire analyzed using SPSS version 25. The research results showed that, partially, the three variables soft skills, interests, and motivation significantly influenced work readiness. Interest is the most dominant variable influencing work readiness, followed by motivation and soft skills. Meanwhile, simultaneously, all three variables were also found to significantly influence Generation Z's work readiness. However, the coefficient of determination was only 22.1%, indicating that there are other variables outside the scope of this study that also influence work readiness. These findings highlight the importance of developing non-academic aspects in education as preparation for the increasingly complex and competitive job market, especially in the digital age, which demands flexibility, creativity, and strong interpersonal skills from every job seeker.